GENDER MAINSTREAMING – AN ETHICAL FEMINIST CONSIDERATION - Karin van Marle (Obiter, 2022)
In this article I tentatively consider the notion of gender mainstreaming from an ethical feminist perspective. Underlying this is a tension, or paradox, between law’s limits and law’s potential, law’s poetry, poetry’s law. A few theoretical arguments come into play. Firstly, the multiple meanings of sex and gender are reconsidered. Thereafter feminist critiques against the notion of one feminist method as well as a feminist jurisprudence are combined with a critical perspective on the institutionalisation of human rights and the politics of law. I recall these arguments to inform my investigation into gender mainstreaming. Two aspects are considered: firstly, in light of the critical perspectives, the preference for gender mainstreaming instead of challenging from the margins; and secondly, how mainstreaming actually takes place. Relying on the notion of ethical feminism and concepts of “asymmetrical reciprocity”, “city life”, the “imaginary domain” and the “community of the ought to be”, I ponder ways of making gender issues noticed beyond and within attempts at mainstreaming.